2021
DOI: 10.1177/17588359211049779
|View full text |Cite
|
Sign up to set email alerts
|

Not all KIT 557/558 codons mutations have the same prognostic influence on recurrence-free survival: breaking the exon 11 mutations in gastrointestinal stromal tumors (GISTs)

Abstract: Background: Although the gastrointestinal stromal tumor (GIST) genotype is not currently included in risk-stratification systems, a growing body of evidence shows that the pathogenic variant (PV) type and codon location hold a strong prognostic influence on recurrence-free survival (RFS). This information has particular relevance in the adjuvant setting, where an accurate prognostication could help to better identify high-risk tumors and guide clinical decision-making. Materials and Methods: Between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our result is not consistent with Incorvaia et al’s result. Although several study groups have reported the poor prognostic role of D-557/8 or deletion in c-KIT exon 11 on recurrence free survival in resected GIST patients, the impact of mutational type of c-KIT exon 11 on survival of advanced GIST patients needs more data for further confirmation [ 32 34 ]. The genetic study for c-KIT and PDGFRA is not routinely performed for GISTs because it is not reimbursed in Taiwan and the application of sunitinib or regorafenib is feasible without genetic data.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is not consistent with Incorvaia et al’s result. Although several study groups have reported the poor prognostic role of D-557/8 or deletion in c-KIT exon 11 on recurrence free survival in resected GIST patients, the impact of mutational type of c-KIT exon 11 on survival of advanced GIST patients needs more data for further confirmation [ 32 34 ]. The genetic study for c-KIT and PDGFRA is not routinely performed for GISTs because it is not reimbursed in Taiwan and the application of sunitinib or regorafenib is feasible without genetic data.…”
Section: Discussionmentioning
confidence: 99%
“…The type of GIST driver mutation represents an important prognostic factor, correlating with clinical features and biological aspects of the disease [5]. The presence of deletions within c-KIT codons 557/558 is associated with a more aggressive behavior compared to other exon 11 mutations, thus resulting in shorter recurrence-free survival (RFS) for patients with resected GIST and shorter PFS for metastatic patients [44,45].…”
Section: Looking Forward: Driver Mutations and Immune Microenvironmentmentioning
confidence: 99%
“…Immune checkpoints, such as PD-L1, PD-1, and CTLA-4, by escaping immune surveillance, play a key role in tumor progression and influence the survival of patients with solid tumors [16,47]. According to the recent knowledge, despite some known limitations, immune checkpoint expression could be a potential prognostic factor and predictive biomarker of response to immune checkpoint inhibitors in patients with solid tumors [45,[48][49][50][51].…”
Section: Driver Mutations and Immune Checkpoint Expression To Improve...mentioning
confidence: 99%
“…GISTs carrying KIT exon 11 mutations with deletions at codon 557 and/or 558 have a poorer prognosis than those with mutations at other sites ( 6–9 ). Deletions at both codons 557 and 558 promote liver metastasis ( 10 ) and are thought to be required for malignant transformation ( 11 ). The malignant progression of GISTs has also been associated with chromosomal changes, including deletions in chromosome arms 1p, 13q, 14q, 15q, and 22q; gains in chromosomes 4 and 5 ( 12–14 ); and genetic alterations, including mutations, copy-number (CN) abnormalities, and aberrant expression of cell cycle–related genes ( p53 , CDKN2A , and RB1 ; ref.…”
Section: Introductionmentioning
confidence: 99%